HPV Vaccination Champions: Evaluating a Technology-Mediated Intervention for Parents - Sundstrom, Beth; Cartmell, Kathleen B.; White, Ashley A.; Russo, Nicole; Well, Henry; Pierce, Jennifer Young; Brandt, Heather M.; Roberts, James R.; Ford, Marvella E. (Frontiers in Digital Health, 2021)
Human papillomavirus (HPV) vaccination prevents 6 HPV-related cancers in men and women. Yet, rates of HPV vaccination among adolescents in the United States lag behind other developed nations, revealing a significant public health issue. This feasibility study tested a collaborative online learning environment to cultivate HPV vaccination champions. A three-month training program recruited parents to serve as proponents and social media influencers to identify solutions to overcome barriers to HPV vaccination. A mixed methods study design included a pretest survey, three online asynchronous focus groups, a posttest survey, as well as a longitudinal follow-up survey at six months. Participants included 22 parents who self-identified as female (95.4%) and white (90.9%). Overall, there was a statistically significant difference in knowledge of HPV and HPV vaccination between pretest and posttest (p-value = 0.0042). This technology-mediated intervention increased parents’ confidence and motivated them to speak more freely about HPV vaccination in-person and online with others in their social networks. Participants identified prevalent misinformation about HPV vaccination and learned how to effectively craft messages to address concerns related to safety and side effects, gender, understanding of risk, and sexual activity. Objective measures and qualitative open-ended assessment showed high intervention engagement and treatment satisfaction. All participants (100%) indicated that they enjoyed participating in the intervention. The effectiveness of this feasibility study suggests that social media is an appropriate platform to empower parents to counter vaccine hesitancy and misinformation through HPV vaccination information that is simple and shareable in-person and online.